2021
DOI: 10.1080/19490976.2021.1941710
|View full text |Cite
|
Sign up to set email alerts
|

“Driver-passenger” bacteria and their metabolites in the pathogenesis of colorectal cancer

Abstract: Colorectal cancer (CRC) is a significant public health problem accounting for about 10% of all new cancer cases globally. Though genetic and epigenetic factors influence CRC, the gut microbiota acts as a significant component of the disease's etiology. Further research is still needed to clarify the specific roles and identify more bacteria related to CRC development. This review aims to provide an overview of the "driver-passenger" model of CRC. The colonization and active invasion of the "driver(s)" bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 113 publications
(164 reference statements)
0
25
0
Order By: Relevance
“…The model suggests that driver bacteria promote the colonization of passenger bacteria by altering the intestinal microenvironment, and differences in the types of driver and passenger bacteria are found at different stages of CRC development. Since then, several studies based on the "driver‐passenger" model have reached consistent conclusions 9,41,42 . Wang Y et al sequenced CRC cancer and paraneoplastic tissues and identified 4 genera and 2 families of potential driver bacteria and 14 genera and 14 families of potential passenger bacteria, suggesting their potential role as predictive markers for the early diagnosis of CRC 9 …”
Section: Intestinal Mucosal Tissue Microbiome and Early Detection Of Crcmentioning
confidence: 89%
See 1 more Smart Citation
“…The model suggests that driver bacteria promote the colonization of passenger bacteria by altering the intestinal microenvironment, and differences in the types of driver and passenger bacteria are found at different stages of CRC development. Since then, several studies based on the "driver‐passenger" model have reached consistent conclusions 9,41,42 . Wang Y et al sequenced CRC cancer and paraneoplastic tissues and identified 4 genera and 2 families of potential driver bacteria and 14 genera and 14 families of potential passenger bacteria, suggesting their potential role as predictive markers for the early diagnosis of CRC 9 …”
Section: Intestinal Mucosal Tissue Microbiome and Early Detection Of Crcmentioning
confidence: 89%
“…Since then, several studies based on the "driver‐passenger" model have reached consistent conclusions. 9 , 41 , 42 Wang Y et al sequenced CRC cancer and paraneoplastic tissues and identified 4 genera and 2 families of potential driver bacteria and 14 genera and 14 families of potential passenger bacteria, suggesting their potential role as predictive markers for the early diagnosis of CRC. 9 …”
Section: Intestinal Mucosal Tissue Microbiome and Early Detection Of Crcmentioning
confidence: 99%
“…ETBF toxin is coded by the bft gene and is highly correlated with diarrhea in humans[ 53 , 54 ]. ETBF can cleave E-cadherin in the epithelial cells, allowing bacterial translocation[ 55 , 56 ]. ETBF induces an IL-17-mediated immune response with the infiltration of lymphocytes and neutrophils and damages the DNA via the formation of microadenoma[ 4 , 53 , 54 ].…”
Section: To the Editormentioning
confidence: 99%
“…A recent manuscript by Avril and DePaolo[ 56 ], identified that the co-colonization of ETBF and Escherichia coli strains, harboring the pks island, promotes the development of intestinal cancer. ETBF promotes the degradation of the intestinal mucus and induction of IL-17-mediated inflammation by the host’s immune cells.…”
Section: To the Editormentioning
confidence: 99%
“…It can metabolize the indigestible components of food, synthesize nutrients for epithelial regeneration, and modulate the immune response to maintain mucosal integrity by protecting against harmful environmental and endogenous toxic stimuli [11][12][13][14] .The initiation and progression of CRC are related to complex biological pathways involving multiple genetic and epigenetic alterations [15][16][17] . Many reports have shown that dysbiosis is closely associated with the initiation and progression of CRC and that the gut microbiome can be a candidate marker for early detection of CRC [18][19][20][21][22][23][24][25] . Therefore, modulation of the gut microbiome has been attempted as an adjunctive therapeutic strategy for CRC, such as increasing the sensitivity of immune checkpoint inhibitors in advanced and metastatic CRC [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%